Adhesive

By using adhesives composed of powder, water, water glass and crosslinking agents, the problems of high cost and low stability of existing formaldehyde-free adhesives are solved, and better adhesive stability and engineering wood product performance are achieved.

CN119895006APending Publication Date: 2025-04-25INSAREC BV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380067083.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-19
Filing Date
2023-09-15
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing formaldehyde-free adhesives used in the production of engineered wood products have problems of high cost, low stability and uneven adhesive distribution.

Method used

A binder containing powder, water, water glass and a crosslinker is used, which consists of carbohydrates and proteins, and water glass acts as a dispersant and hardener for the binder. Crosslinkers such as isocyanates are used to improve the bonding strength.

Benefits of technology

It realizes better stability and processability of the adhesive, reduces the amount of crosslinking agent used, and improves the water resistance and mechanical properties of engineered wood products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005317983070000131
    Figure BDA0005317983070000131
  • Figure BDA0005317983070000161
    Figure BDA0005317983070000161
  • Figure BDA0005317983070000171
    Figure BDA0005317983070000171
Patent Text Reader

Abstract

The invention relates to an adhesive, a method for the production thereof and a product obtained by means of the adhesive. The binder at least contains powder, water, water glass and a cross-linking agent. The powder contains carbohydrates and proteins. The ratio of the mass of the powder to the mass of the solid of the water glass is between 50: 1 and 2: 1.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to adhesives for use in bonding particles, fibers, layers, bundles or components, such as to produce engineered wood products, and to methods of making the adhesives. The present invention also relates to products bonded with the adhesives; and methods of bonding such products with the adhesives.

[0002] In engineered wood products, adhesives are used to connect wood particles, wood fibers, wood bundles, wood layers and / or other wood components or components. Examples of such engineered wood products are particleboard, wood fiberboard (e.g. MDF-Medium Density Fiberboard and HDF-High Density Fiberboard, OSB-Oriented Strand Board) and laminates.

[0003] Cellulosic fibers or cellulose products can also be combined into boards. Non-limiting examples are bamboo, straw, hemp fibers or hemp bundles, kenaf.

[0004] The most common adhesives used in the production of engineered wood products are aminoplast polymers, produced via the polycondensation reaction of urea and formaldehyde to form urea-formaldehyde resins (UF resins). Optionally, melamine is added and melamine-urea-formaldehyde resins (MUF resins) are obtained, or melamine and phenol are added to form melamine-urea-phenol-formaldehyde resins (MUPF resins). The main advantages of formaldehyde-based adhesives are their low cost (due to the use of cheap raw materials in their preparation) and their high reactivity. The disadvantage of such adhesives in engineered wood products is that they emit formaldehyde during and after polymerization. As a result, more and more people are looking to limit formaldehyde emissions or even reduce formaldehyde emissions to zero. This is why formaldehyde-free adhesives for the production of engineered wood products are sought after.

[0005] US 2006 / 0163769 describes the use of water glass as a binder in the production of fire-resistant engineered wood products.

[0006] Known formaldehyde-free adhesives for use in the production of engineered wood products consist of the polymer methylene diphenyl diisocyanate (pMDI). These pMDI adhesives result in wood products with high strength and good water resistance. However, these adhesives have a number of disadvantages. Firstly, they are much more expensive than the conventionally used aminoplasts; this leads to a significant increase in the costs of engineered wood products. On the other hand, such adhesives have a lower stability than the classic aminoplasts, have a strong tendency to stick to process equipment (which, among other things, requires frequent cleaning of the process equipment) and can result in the release of isocyanate monomers during application. This has an adverse effect on the efficiency of the production process of engineered wood products.

[0007] The pMDI adhesive has better bond strength than the conventionally used aminoplasts, so that less adhesive is required. However, this can be disadvantageous because a smaller amount of adhesive can lead to inadequate distribution of the adhesive over the substrate.

[0008] US4190459A describes a method for producing a mineral fiber mat for use as an insulating material. The mineral fibers are linked together by a binder, which is applied in the form of an emulsion of so-called water glass and isocyanate. US4190459A proposes the use of water glass with a solids content of between 40 and 55% by mass. The so-called emulsion mentioned in US4190459A has an initial viscosity of 10000 mPa.s. However, this so-called emulsion is unstable because the viscosity increases rapidly over time.

[0009] CA2019382A1 mentions US4190459A in its prior art section and states that the emulsion described in US4190459A has limited stability. CA2019382A1 describes that a mixture of isocyanate and a sufficient amount of metal soap is used as an adhesive in engineered wood products. Metal soap is used as a barrier compound to prevent the reaction between water and isocyanate, so a sufficient amount of metal soap is required. In addition, CA2019382A1 describes that water glass can also be blended into a mixture of isocyanate and a sufficient amount of metal soap to form an emulsion.

[0010] WO2022 / 049513A1 describes an adhesive for engineered wood products. The adhesive is an emulsion of an isocyanate in water. The isocyanate contains one or more of a diisocyanate, a polyisocyanate, a derivative of a diisocyanate or a derivative of a polyisocyanate. The emulsion also contains water glass. The ratio of the combined mass of water and water glass on the one hand to the mass of isocyanate on the other hand in the emulsion is preferably between 1.2 and 6.

[0011] The object of the present invention is to provide a formaldehyde-free adhesive which is suitable for bonding natural substrates and which can be easily used as an adhesive in the production of engineered wood products such as particleboard, wood fiberboard (such as MDF-boards and HDF-boards), OSB-boards and laminates.

[0012] To achieve this goal, the present invention comprises different aspects.

[0013] The first aspect of the present invention is an adhesive. The adhesive is characterized in that the adhesive contains at least powder, water, water glass and a cross-linking agent; wherein the powder contains carbohydrates and proteins. Water glass is a combination of Na2O and SiO2 in water. The ratio of the mass of the powder to the mass of the solid of the water glass is between 50:1 and 2:1, preferably between 30:1 and 3:1.

[0014] In the context of the present invention, the terms "binder" and "adhesive" are used synonymously for compounds that have a degree of adhesive properties, essentially the ability to provide a bond between two or more pieces of material. Likewise, the terms "bonding" and "bonding" are used synonymously for the act of providing a bond between two or more pieces of material.

[0015] The adhesive is formaldehyde-free, stable, easy to produce and can be easily used as an adhesive in the production of engineered wood products such as particleboard, wood fiberboards (such as MDF-boards and HDF-boards), OSB-boards and laminates.

[0016] The ratio of the mass of the powder of the adhesive of the first aspect of the present invention to the mass of the solid of the water glass provides better stability of the adhesive, imparting good processability to the adhesive.

[0017] As mentioned above, water glass is a combination of Na2O and SiO2 in water. The (molar) ratio between SiO2:Na2O and the mass of solid water glass (in water) can vary. For example, water glass 2.0 has a SiO2:Na2O molar ratio of 2.0:1. Thus, 1 gram of water glass 2.0 (with a solid content of 40% by mass) contains 0.13 grams of solid Na2O. For example, water glass 3.4 has a SiO2:Na2O molar ratio of 3.4:1. Thus, 1 gram of water glass 3.4 (with a solid content of 37% by mass) contains 0.084 grams of solid Na2O. Solid sodium silicate typically has a high Na2O content, which dissolves in water, corresponding to water glass 1.0 to 1.5, or in other words a SiO2:Na2O molar ratio of 1.0:1 to 1.5:1.

[0018] In the context of the present invention, "solid content" refers to the mass percentage of solids, unless otherwise specified.

[0019] A preferred embodiment of the first aspect of the invention is characterized in that the ratio of the mass of powder to the mass of solid Na2O of waterglass is between 140:1 and 6:1, preferably between 80:1 and 10:1, more preferably between 60:1 and 15:1.

[0020] The ratio of the mass of the powder according to this embodiment of the invention to the mass of solid Na2O of waterglass also ensures good water resistance of the engineered wood products bonded with this adhesive.

[0021] In the first aspect of the invention, the powder preferably consists essentially of protein and carbohydrates. The powder may also contain a certain amount of water, ie the powder itself feels dry.

[0022] Typically, powders have only limited solubility in water. As a result, a suspension with sufficiently low viscosity and sufficiently high solids content can be obtained. The adhesive with low viscosity can be distributed adequately on the substrate, for example by spraying or sprinkling the adhesive. In principle, the adhesive can always have a sufficiently low viscosity by adding sufficient water, but excess water leads to excessive pressure buildup when pressing the bonded substrate, which can cause cracks in the cured substrate.

[0023] The use of carbohydrates (e.g. starch) and proteins as adhesives is known individually. Before the development of adhesives based on formaldehyde, proteins (e.g. gelatin) were often used as adhesives. Starch is also often used as an adhesive in the paper industry, for example, to bond different paper layers together. However, the starch is first boiled so that the crystalline phase of the starch is destroyed and the adhesive power of the starch is increased. In all these cases, an adhesive with a low solids content and a high viscosity is obtained.

[0024] The object of the present invention is precisely to prepare an adhesive in which the carbohydrates present retain their crystalline structure. In addition, the protein present in the powder ensures further insolubility of the powder in water at temperatures below 50° C. At higher temperatures (preferably greater than 60° C.), the crystalline structure of the carbohydrates can be destroyed and the affinity of the powder for water increases, with a significant increase in viscosity.

[0025] The adhesive can be produced by initially placing the powder in an aqueous suspension, preferably by high shear or turbulence. Since the powder has limited solubility in water due to its composition, a suspension with a high solids content can be obtained, while the viscosity is limited. As mentioned before, low viscosity is important for being able to distribute the resulting adhesive well over the substrate, for example by spraying the adhesive.

[0026] In the next stage of producing the adhesive according to the invention, water glass can be added to the aqueous suspension of the powder. The water glass interacts with the powder. This leads to a moderate increase in viscosity and activation of the powder. This activation also ensures that the dispersibility of the powder is improved and the addition of a crosslinking agent at a later stage leads to a homogeneous and stable suspension.

[0027] In the next process step, a crosslinker capable of reacting both with the substrate and with the powder can be added to the aqueous suspension of powder and waterglass. Preferably, crosslinkers containing isocyanate, epoxy, azetidinium and / or cyclic anhydride groups are used.

[0028] An important advantage of the present invention is that a stable suspension of the crosslinking agent (eg isocyanate) in water is obtained. The combination of powder and waterglass thus acts as a dispersant for the crosslinking agent.

[0029] The addition of water glass provides the powder with an increased bonding strength. After the adhesive is applied, pressure is applied at elevated temperature. At this elevated temperature, the proteins of the powder denature and the carbohydrates lose their crystallinity. At this elevated temperature, functional groups are also released, primarily on the proteins, as a result of which the water glass connected to the powder undergoes a hardening reaction. These functional groups are therefore hidden at low temperatures and are only expressed when the adhesive is heated to a temperature greater than 50°C.

[0030] Since the cheap waterglass will also contribute to the bond strength, the amount of expensive crosslinking agent can be kept limited. The amount of waterglass is therefore preferably selected so that it acts not only as a dispersant but also to a large extent as an adhesive component. This allows the use of less crosslinking agent and thus a cheaper adhesive (and cheaper engineered wood products produced using such adhesives) which can be dosed reasonably and evenly distributed.

[0031] An important advantage of the present invention is that the crosslinking agent not only acts as a chain extender for the powder, but is also able to react with the hydroxyl groups of the substrate (eg wood) to improve the bond strength.

[0032] Waterglass can also lead to an improvement in the reactivity of the hydroxyl groups of the wood on the one hand and of the crosslinking agent (e.g. isocyanate) on the other hand. Waterglass thus acts not only as an emulsifier for the crosslinking agent (e.g. isocyanate). When the adhesive is used and the temperature is simultaneously increased and after evaporation of the water, the suspension is disrupted and the waterglass can act as a catalyst for the reaction of the crosslinking agent (e.g. isocyanate) with the hydroxyl groups of the wood.

[0033] Preferred embodiments of the first aspect of the invention are characterized in that the powder containing carbohydrates and proteins is obtained by grinding plant raw materials such as cereals (e.g. wheat, rye, barley, millet, rice or oats), corn, sugar beets, nuts (e.g. palm nuts or coconut), seeds (e.g. rapeseed, linseed or sunflower seeds) or legumes (e.g. soybeans, peas, lentils, beans); or the powder containing carbohydrates and proteins is a combination of two or more of these.

[0034] These are readily available raw materials from which powders can be extracted. An important advantage is also that different raw materials can be used. The production of the adhesive according to the invention is therefore not limited to one specific raw material.

[0035] A more preferred embodiment of the first aspect of the invention is characterized in that the powder is obtained by grinding pulse beans, such as soybeans, peas, lentils, beans.

[0036] Preferred embodiments of the first aspect of the invention are characterized in that the powder is a starch and / or flour, such as cereal starch and / or flour (e.g. wheat, rye, barley, millet, rice or oats), low-grade flour, corn starch and / or flour, beet starch and / or flour, nut starch and / or flour (e.g. palm nut or coconut), seed starch and / or flour (e.g. from rapeseed, linseed or sunflower seeds) or legume starch and / or flour (e.g. from soya, peas, lentils, beans); or the powder is a combination of two or more of these.

[0037] As is commonly known, the terms "starch" and "flour" are used interchangeably for powders obtained from grinding plant material.

[0038] A more preferred embodiment of the first aspect of the invention is characterized in that the powder is a bean starch and / or flour, such as soya flour, pea starch, broad bean starch, or a combination of two or more of these.

[0039] Flour and starch are readily available. An important advantage is also that different types of flour and / or starch can be used. The production of the adhesive according to the invention is therefore not limited to one specific raw material or flour and / or starch type.

[0040] A particularly interesting type of flour for use in the present invention is the so-called "low-grade flour", which is a residual material from wheat flour production. Due to the browner color of low-grade flour, this product is declared unsuitable for the production of wheat bread and is processed as animal feed. Low-grade flour has a higher protein to carbohydrate ratio than the cereal from which it is obtained. Without wishing to be bound by any theory, the inventors suspect that a higher protein to carbohydrate ratio may lead to better binding properties.

[0041] A preferred embodiment of the first aspect of the invention is characterized in that the powder in water is obtained by a process involving fermentation of plant material.

[0042] This allows to prepare powders from residual streams of the agricultural industry and thus improve the value of these residual streams. In such a fermentation process, microorganisms (such as fungi or bacteria) convert natural raw materials into powders in aqueous suspension. These powders have a homogeneous combination of carbohydrates and proteins.

[0043] Preferred embodiments of the first aspect of the invention are characterized in that the ratio of the mass of protein to the mass of carbohydrates in the powder is between 2:1 and 1:30, preferably between 1.5:1 and 1:15, more preferably between 1:2 and 1:10.

[0044] A preferred embodiment of the first aspect of the invention is characterized in that the viscosity of the adhesive at 25° C. is less than 1000 mPa.s, preferably less than 500 mPa.s.

[0045] Adhesives with such viscosity values ​​ensure good distribution of the adhesive over the products to be bonded. Due to its low viscosity, the adhesive can also be applied by spraying. These viscosity values ​​also ensure good penetration of the adhesive into the pores of the products to be bonded. Due to the low viscosity, the processability of the adhesive is therefore better.

[0046] A preferred embodiment of the first aspect of the invention is characterized in that the powder, water, water glass and crosslinking agent are uniformly distributed in the binder.

[0047] This embodiment has the advantage that the adhesive can be used as a one-component system. The adhesive can be stored and easily used without further restrictions.

[0048] A preferred embodiment of the first aspect of the invention is characterized in that the adhesive is a two-component adhesive; having a first component and a second component, wherein the first component is different from the second component in the presence of a powder and a crosslinking agent, respectively.

[0049] The first component may contain no water glass, or contain a portion of water glass or the entire amount of water glass. If the first component contains a portion of water glass or the entire amount of water glass, this facilitates dispersion of the powder.

[0050] The second component may contain no water glass, or contain a portion of water glass or the entire amount of water glass. If the second component contains a portion of water glass or the entire amount of water glass, this promotes the emulsification of the crosslinking agent in the second component.

[0051] In the case of a two-component adhesive, the two components can be stored separately and mixed when the adhesive is needed; or applied separately to the products to be bonded. Separate storage of the two components of the (two-component) adhesive provides an extended shelf life of the adhesive.

[0052] A preferred embodiment of the first aspect of the invention is characterized in that the solids content of the binder is between 10% and 40% by mass, preferably between 15% and 35% by mass.

[0053] The adhesive according to this embodiment is easy to process and does not require the transportation of excessive water when transporting the adhesive.

[0054] A preferred embodiment of the first aspect of the invention is characterized in that the crosslinking agent is a product containing at least two isocyanate groups, preferably wherein the crosslinking agent contains one or more of a diisocyanate, a polyisocyanate, a derivative of a diisocyanate or a derivative of a polyisocyanate.

[0055] Such cross-linking agents are readily available. Furthermore, limited amounts of such cross-linking agents are sufficient.

[0056] A preferred embodiment of the first aspect of the invention is characterized in that the crosslinking agent is a derivative or a polymer of methylene diphenyl diisocyanate (MDI), preferably polymeric methylene diphenyl diisocyanate (pMDI).

[0057] Such cross-linking agents are also readily available, and again limited amounts of such cross-linking agents are sufficient.

[0058] In principle, various types of isocyanates can be used in the present invention. However, polymer methylene diphenyl diisocyanate (pMDI) is preferred. Unlike many other isocyanates, polymer methylene diphenyl diisocyanate (pMDI) has little compatibility with water or even no compatibility with water. In many types of isocyanates, water reacts with isocyanate groups, resulting in the release of carbon dioxide. Because polymer methylene diphenyl diisocyanate (pMDI) and water show little compatibility or no compatibility, there is only limited reaction when water and polymer methylene diphenyl diisocyanate (pMDI) contact. This is caused by the following fact: when water and polymer methylene diphenyl diisocyanate (pMDI) mix and stop mixing, water and polymer methylene diphenyl diisocyanate (pMDI) separate from each other. However, using powder according to the present invention and water glass makes the suspension stable.

[0059] Furthermore, polymeric methylene diphenyl diisocyanate (pMDI) has a large number of reactive groups per molecule. This is advantageous for the bond strength, since a crosslinked, dense network is obtained. Polymeric methylene diphenyl diisocyanate (pMDI) is also the cheapest choice of commercially available isocyanates.

[0060] Because of these aspects, polymeric methylene diphenyl diisocyanate (pMDI) allows the advantages of the suspension according to the invention to be achieved in an optimal manner, with low costs for the binder and the products bonded therewith.

[0061] A preferred embodiment of the first aspect of the invention is characterized in that the crosslinking agent is a product containing at least two epoxy groups, or at least two cyclic anhydride groups, or at least two azetidine functional groups; or a mixture of two or more of these products.

[0062] These crosslinkers are products containing functional groups that are highly reactive with hydroxyl and / or carboxyl groups.

[0063] Examples of crosslinking agents containing at least two epoxy groups and which can therefore be used in the present invention are bisphenol A (BPA) diepoxide, glycidyl cyclohexene oxide, epoxidized soybean oil or linseed oil, multifunctional glycidyl ethers or esters. Examples of crosslinking agents containing azetidinium are those used in the paper industry to make paper stronger primarily under wet conditions, such as Kymene 557H. Examples of crosslinking agents containing cyclic anhydrides are maleated oils such as those derived from soybean oil or linseed oil.

[0064] An advantage is that different types of cross-linking agents can be used. The present invention is not limited to the use of one type of cross-linking agent.

[0065] Preferred embodiments of the first aspect of the invention are characterized in that the ratio of the mass of crosslinker to the mass of powder is between 1:15 and 2:1, preferably between 1:10 and 1:1, more preferably between 1:8 and 1:1.25, even more preferably between 1:2.5 and 1:1.5.

[0066] The amount of crosslinking agent used in the adhesive can thus be limited. This reduces the price of the adhesive, since the crosslinking agent represents the most expensive component in the adhesive.

[0067] A preferred embodiment of the first aspect of the invention is characterized in that the adhesive contains a thermoplastic adhesive component, preferably a biorenewable thermoplastic adhesive component, such as an aqueous dispersion of natural rubber latex or polylactic acid.

[0068] The adhesive can be tailored for specific applications. The use of thermoplastic adhesive components allows the amount of crosslinking agent to be reduced. Furthermore, the use of biorenewable thermoplastic adhesive components ensures the "natural" nature of the adhesive.

[0069] A preferred embodiment of the first aspect of the invention is characterized in that the molar ratio of SiO2 to Na2O in the waterglass is between 4 and 1.5, preferably between 3.8 and 2.0, more preferably between 3.5 and 2.5, even more preferably between 3.5 and 2.8.

[0070] It appears that the use of the adhesive according to this embodiment results in a higher water fastness of the bonded product. The relatively small amount of Na2O relative to the amount of SiO2 in the waterglass appears to achieve this feature.

[0071] A preferred embodiment of the first aspect of the invention is characterized in that the adhesive contains one or more of a water-resistant additive, a catalyst, a dye, a pigment, a flame retardant, a cold tack improver, or a foaming agent.

[0072] The adhesive may contain such additives to impart specific properties to the bonded product and / or to improve the processability of the adhesive. Examples of water-repellents that can be used are wax emulsions (e.g. based on paraffin or hydrogenated vegetable oils), olefin-ketene dimers and alkyl succinic anhydrides. Preferably, these water-repellents are added in the form of emulsions. Examples of catalysts that accelerate and improve the reaction between the hydroxyl groups of the wood and the isocyanate crosslinking agents (e.g. pMDI) are tertiary amines and tin derivatives; these products are well known in the polyurethane industry.

[0073] A preferred embodiment of the first aspect of the invention is characterized in that the particle size distribution by volume of the powder measured by laser diffraction (Beckman Coul ter laser diffraction apparatus LS13 320) in aqueous dispersion is D 50 The value is less than 200 microns, preferably less than 100 microns, more preferably less than 50 microns, and even more preferably less than 30 microns. 50 The value is the particle size (expressed in microns) where 50% of the particles are smaller than this value.

[0074] These embodiments provide better adhesive stability and good adhesive efficiency.

[0075] A preferred embodiment of the first aspect of the invention is characterized in that the particle size distribution by volume of the powder measured by laser diffraction in aqueous dispersion is D 90 The value is less than 200 microns, preferably less than 100 microns. 90 The value is the particle size (expressed in microns) where 90% of the particles are smaller than this value.

[0076] In a further aspect, the present invention provides a method of preparing an adhesive as described herein, the method comprising the steps of:

[0077] - mixing powder and water to obtain a first aqueous suspension;

[0078] - adding waterglass and a crosslinking agent to the first aqueous suspension; and

[0079] - further mixing the resulting suspension to obtain a binder;

[0080] wherein the powder contains carbohydrates and proteins; wherein the water glass contains a combination of Na2O and SiO2; and wherein the ratio of the mass of the powder to the mass of the solid of the water glass is between 50:1 and 2:1, preferably between 30:1 and 3:1.

[0081] A preferred embodiment of the process for preparing the adhesive according to the invention is characterized in that powder and water are mixed by high shear or turbulence.

[0082] A preferred embodiment of the process for preparing the adhesive according to the invention is characterized in that water glass is first added to the first aqueous suspension and mixed with the first aqueous suspension before the addition of the crosslinker.

[0083] As mentioned above, the affinity of the powder may increase at elevated temperatures, e.g., 60° C. or higher, resulting in increased viscosity. In order to avoid or minimize an increase in viscosity, it may be preferred to maintain the temperature during the process steps below 60° C., e.g., below 50° C., below 40° C., and even below 30° C. The temperature may be maintained by any suitable means known in the art, such as a cooling device.

[0084] A preferred embodiment of the process for preparing the binder according to the invention is characterized in that the temperature during preparation of the first aqueous suspension and / or the binder is maintained below 60°C, preferably below 50°C, more preferably below 40°C, even more preferably below 30°C.

[0085] It may be advantageous for the bond strength of the adhesive if the adhesive is applied to the substrate or mixed with the substrate soon after the crosslinker has been added to the powder, waterglass and water (e.g. within 1 hour, within 50 min, within 40 min, within 30 min, or even within 10 min after the crosslinker has been added to the other components of the adhesive). By using the adhesive soon after the crosslinker has been added to the powder, waterglass and water, less crosslinker may have reacted with the powder and thus more crosslinker may still be available to react with the hydroxyl groups of the substrate (e.g. wood).

[0086] In a further aspect, the present invention provides an adhesive prepared according to a method as defined herein.

[0087] In yet another aspect, the invention provides a product. The product contains particles, fibers, layers, bundles or components; wherein the particles, fibers, layers, bundles or components are bonded together using a binder according to any one of the embodiments of the first aspect of the invention in a pressing process at elevated temperature, wherein water evaporates from the binder and the binder provides bonding of the particles, fibers, layers, bundles or components. In the product, the mass ratio of the total amount of particles, fibers, layers, bundles or components to the solid content of the binder is between 99:1 and 92:8, preferably between 98:2 and 95:5.

[0088] A preferred embodiment of the product according to the invention is characterized in that the mass ratio of the solids of the crosslinking agent in the adhesive to the total amount of particles, fibers, layers, bundles of the product is between 0.5% and 2% by mass, preferably between 0.75% and 1.75% by mass, more preferably between 1% and 1.5% by mass.

[0089] As mentioned previously, the inexpensive water glass contributes to the bond strength, which allows the use of smaller amounts of expensive cross-linking agents in the adhesive relative to the total amount of particles, fibers, layers, bundles in the product.

[0090] The adhesive does not contain formaldehyde. Small amounts of adhesive can be used to achieve bonding.

[0091] Preferably, the product is a board, such as a wood fiber board (such as an MDF board or an HDF board), a particleboard, an OSB (oriented strand board) board or a laminate. The product can also be a molded part, in which the bonded wood components are pressed into the desired shape in a mold, for example for the preparation of pallet blocks.

[0092] In a preferred embodiment of the invention, the particles, fibers, layers, bundles or components are wood-based or cellulose-based, such as bamboo, straw, reed, hemp, palm, miscanthus, bagasse, molasses, or agricultural waste streams.

[0093] The adhesive appears to be particularly suitable for bonding together wood components such as wood chips, wood bundles or wood fibers.

[0094] The final aspect of the present invention relates to a method for preparing the product. The method comprises the following steps:

[0095] - providing a quantity of particles, fibers, layers, bundles or components;

[0096] - applying a binder according to any one of the embodiments of the first aspect of the invention to particles, fibres, layers, bundles or components;

[0097] - shaping the particles, fibers, layers, bundles or mixture of components and binder, for example in the form of a sheet;

[0098] - Curing the binder at elevated temperature and under pressure, wherein water evaporates from the binder and wherein curing of the binder results in a product in which particles, fibers, layers, bundles or components are bound together by the binder.

[0099] In principle, the product is obtained by pressing the bonded wood components with heated pressing plates, but for thicker products or mouldings additional heating can be used via injection of steam.

[0100] The binder contains no formaldehyde and can be easily used in the process.

[0101] Preferably, the particles, fibers, layers, bundles or components are wood-based or cellulose-based, such as bamboo, straw, reed, hemp, palm, miscanthus, bagasse, molasses, or agricultural waste streams.

[0102] The adhesive appears to be particularly suitable for bonding together wood components such as wood chips, wood bundles or wood fibers.

[0103] A preferred embodiment of the process for preparing the product according to the invention is characterized in that in the product the mass ratio of the total amount of particles, fibers, layers, bundles or components to the solids content of the binder is between 99:1 and 92:8, preferably between 98:2 and 95:5.

[0104] It is thus possible to work with a limited amount of adhesive relative to the mass of the components to be bonded together.

[0105] A preferred embodiment of the process for producing the product according to the invention is characterized in that the product is a board, for example a wood fiberboard (for example an MDF board or an HDF board), a particleboard, an OSB (Oriented Strand Board) board or a laminate.

[0106] Adhesives are particularly suitable for such products. The panels obtained have good mechanical properties; and are also resistant to water.

[0107] As mentioned above, it may be advantageous for the bond strength of the adhesive, and subsequently the tensile strength of the bonded product, if the adhesive is applied to or mixed with the substrate shortly after the crosslinking agent has been added to the powder, waterglass and water.

[0108] A preferred embodiment of the process for preparing the product according to the invention is characterized in that the binder is applied to the particles, fibers, layers, bundles or components within 1 hour, preferably within 50 min, more preferably within 40 min, even more preferably within 30 min after the crosslinking agent has been added to the powder, water glass and water.

[0109] Materials used

[0110]

[0111] Waterglass 2.0 (solid content 40 mass %) was obtained from PQ Chemicals and had a SiO2:Na2O molar ratio of 2.0:1. Waterglass 3.4 (solid content 37 mass %) was also obtained from PQ Chemicals and had a SiO2:Na2O molar ratio of 3.4:1. I-Bond PB PM 4350 (pMDI) was obtained from Huntsman. 40% wax emulsion Vivas tar 9061 was obtained from H&R, the Netherlands. Example

[0112] Example 1

[0113] In a first embodiment according to the invention, a suspension is obtained by mixing 10 grams of rye flour (90% by mass solids) with 60 grams of water under high shear. Then 2.5 grams of waterglass 2.0 (40% by mass solids solids) corresponding to 0.33 grams of Na2O solids and 5.5 grams of pMDI are added to the suspension and mixed. The resulting adhesive (suspension) has good physical stability and a viscosity of 150 mPa.s (measured at 25°C).

[0114] First 7.5 grams of Vivas tar 9061 were added to 450 grams of wood chips and mixed, and then the suspension as described above was added and mixed. After the entire mixture had been mixed for 2 minutes, the bonded chips were placed in a molding and the resulting mat was pressed at 200° C. for 2 minutes to form a 13 mm thick and 680 kg / m 3 The internal tensile strength of the sheet is 0.50N / mm 2 And the degree of swelling after immersion in water for 2 hours was 10%.

[0115] Example 2

[0116] In a second example according to the invention, the bonded crumbs as described in Example 1 were first stored at 25° C. for 30 min and then pressed according to the same conditions as in Example 1. The measured tensile strength was 0.48 N / mm 2 And the degree of swelling after immersion in water for 2 hours was 11%.

[0117] Example 3

[0118] In a third example according to the invention, the procedure of Example 1 was repeated, but 10 g of pea starch E1370D was used instead of rye flour. The resulting adhesive (suspension) had good physical stability and a viscosity of 130 mPa.s (measured at 25° C.).

[0119] For a density of 700 kg / m 3 For a plate with a thickness of 12 mm, the measured tensile strength and swelling degree are 0.52 N / mm 2 and 6%.

[0120] The particle size distribution by volume of the powder used in the third example measured by laser diffraction in an aqueous dispersion is D 50 The value is 29.8 micrometers. The particle size distribution by volume of the powder used in the third example measured by laser diffraction in an aqueous dispersion is D 90 The value is 67.4 microns.

[0121] Example 4

[0122] In a fourth embodiment according to the invention, the procedure of embodiment 1 was repeated, but 10 g of pea starch F70D was used instead of rye flour; and 80 g of water was used instead of 60 g. The resulting adhesive (suspension) had good physical stability and a viscosity of 400 mPa.s (measured at 25° C.). For a density of 680 kg / m 3 For a plate with a thickness of 13 mm, the measured tensile strength and swelling degree are 0.58 N / mm 2 and 6%.

[0123] Comparative Example 5

[0124] In Comparative Example 5, the procedure of Example 1 was repeated, but no water glass was added. The resulting suspension had poor physical stability. After a few minutes, drops of pMDI became visible in the suspension, indicating phase separation. For a density of 680 kg / m 3 For a plate with a thickness of 13 mm, the measured tensile strength and swelling degree are 0.15 N / mm 2 and 20%.

[0125] Example 6

[0126] In a sixth example according to the invention, the procedure of Example 1 was repeated, but the first component of the adhesive was obtained by mixing 10 grams of rye flour (90% solids) with 35 grams of water under high shear. The second component of the adhesive was obtained separately by mixing 25 grams of water, 2.5 grams of waterglass 2.0 and 5.5 grams of pMDI under high shear to provide an emulsion.

[0127] After adding the wax emulsion to the wood chips according to Example 1, the first component and the second component were separately dosed onto the wood chips and mixed thoroughly for 2 minutes. 3 The measured tensile strength and swelling degree of the obtained particleboard plywood were 0.45 N / mm 2 and 14%.

[0128] Example 7

[0129] In a seventh embodiment according to the invention, the procedure of embodiment 1 was repeated, but a suspension was obtained by mixing 10 grams of broad bean starch with 60 grams of water under high shear. Then 4.0 grams of water glass 3.4 (solid content 37% by mass) corresponding to 0.34 grams of Na2O solids and 4.5 grams of pMDI were added to the suspension and mixed. The resulting adhesive (suspension) had good physical stability and a viscosity of 160 mPa.s (measured at 25° C.).

[0130] For a density of 610 kg / m 3 The measured tensile strength and swelling degree of the obtained particleboard plywood were 0.46 N / mm and 12 mm thick respectively. 2 and 7%.

[0131] The particle size distribution by volume of the powder used in the seventh example measured by laser diffraction in aqueous dispersion is D 50 The value is 28.4 micrometers. The particle size distribution by volume of the powder used in the seventh example measured by laser diffraction in an aqueous dispersion is D 90 The value is 87.9 microns.

[0132] Example 8

[0133] In an eighth example according to the invention, the procedure of Example 1 was repeated, but 6 g of water glass 2.0 (solid content 40%) and 4.5 g of pMDI were used, corresponding to 0.79 g of Na2O solid. The resulting adhesive (suspension) had good physical stability and a viscosity of 140 mPa.s (measured at 25° C.). For a density of 680 kg / m 3 For a plate with a thickness of 12 mm, the measured tensile strength and swelling degree are 0.45 N / mm 2 and 15%.

[0134] Examples 9-10

[0135] In the ninth and tenth examples according to the present invention, the procedure of Example 1 was repeated, but low-grade flours having different particle sizes were used as powders.

[0136] For this purpose, 10 g of low-grade flour (1 or 2) were suspended in 60 g of water, and then 4.0 g of waterglass 3.4 and 4.5 g of pMDI were added. Both mixtures had good physical stability.

[0137] First 10 g of Vivas tar 9061 were added to 450 g of wood chips and mixed, and then the suspension as described above was added and mixed. The bonded chips were pressed at 200° C. for 2 minutes. The resulting particleboards with a thickness of 13 mm all showed a swelling degree of 6% after immersion in water for 2 hours. The tensile strength of the particleboard with low-grade flour 1 was 0.38 N / mm 2 , while the tensile strength of the particleboard with low-grade flour 2 is 0.58N / mm 2 The density of both boards is 615kg / m 3 .

[0138] The following table gives an overview of the adhesives according to different examples, the various parameters of the composition and viscosity of the adhesives, and the tensile strength and swelling of the products made with the adhesives.

[0139] Embodiment Overview

[0140]

[0141]

[0142]

Claims

1. Adhesive, characterized in that The adhesive contains at least powder, water, water glass and a cross-linking agent; wherein the powder contains carbohydrates and proteins; wherein the water glass contains a combination of Na2O and SiO2; The ratio of the mass of the powder to the mass of the solid of the water glass is between 50:1 and 2:1, preferably between 30:1 and 3:

1.

2. The adhesive according to claim 1, characterized in that The ratio of the mass of the powder to the mass of the solid Na2O of the water glass is between 140:1 and 6:1, preferably between 80:1 and 10:1, more preferably between 60:1 and 15:

1.

3. The adhesive according to any one of the preceding claims, characterized in that The powder is obtained by grinding plant materials such as cereals (e.g. wheat, rye, barley, millet, rice or oats), corn, sugar beets, nuts (e.g. palm nuts or coconut), seeds (e.g. rapeseed, linseed or sunflower seeds) or legumes (e.g. soybeans, peas, lentils, beans); or the powder is a combination of two or more of these.

4. The adhesive according to any one of the preceding claims, characterized in that The powder is a flour, such as cereal flour (e.g. wheat, rye, barley, millet, rice or oats), plain flour, corn flour, beet flour, nut flour (e.g. palm nut or coconut), seed flour (e.g. from rapeseed, linseed or sunflower seeds) or legume flour (e.g. from soya, peas, lentils, beans); or the powder is a combination of two or more of these.

5. The adhesive according to any one of the preceding claims, characterized in that The powder in water is obtained by fermentation of plant material.

6. The adhesive according to any one of the preceding claims, characterized in that In the powder, the ratio of the mass of the protein to the mass of the carbohydrates is between 2:1 and 1:30, preferably between 1.5:1 and 1:15, more preferably between 1:2 and 1:

10.

7. The adhesive according to any one of the preceding claims, characterized in that The viscosity of the adhesive at 25° C. is less than 1000 mPa.s, preferably less than 500 mPa.s.

8. The adhesive according to any one of the preceding claims, characterized in that The powder, the water, the water glass and the cross-linking agent are uniformly distributed in the adhesive.

9. The adhesive according to any one of the preceding claims 1 to 7, characterized in that The adhesive is a two-component adhesive having a first component and a second component; wherein the first component contains the powder, a portion of the water and the entire amount of the water glass or a portion of the water glass or no water glass; The second component contains the crosslinking agent, a portion of the water and the whole amount of the water glass or a portion of the water glass or no water glass.

10. The adhesive according to any one of the preceding claims, characterized in that The solid content of the binder is between 10% and 40% by mass, preferably between 15% and 35% by mass.

11. The adhesive according to any one of the preceding claims, characterized in that The crosslinking agent is a product containing at least two isocyanate groups, and preferably the crosslinking agent contains one or more of diisocyanate, polyisocyanate, diisocyanate derivatives or polyisocyanate derivatives.

12. The adhesive according to any one of the preceding claims, characterized in that The crosslinking agent is a derivative or polymer of methylene diphenyl diisocyanate (MDI), preferably polymer methylene diphenyl diisocyanate (pMDI).

13. The adhesive according to any one of the preceding claims, characterized in that The crosslinking agent is a product containing at least two epoxy groups, or at least two cyclic anhydride groups, or at least two azetidine functional groups; or a mixture of two or more of these products.

14. The adhesive according to any one of the preceding claims, characterized in that The ratio of the mass of the crosslinking agent to the mass of the powder is between 1:15 and 2:1, preferably between 1:10 and 1:1, more preferably between 1:8 and 1:1.25, even more preferably between 1:2.5 and 1:1.

5.

15. The adhesive according to any one of the preceding claims, characterized in that The adhesive contains a thermoplastic adhesive component, preferably a biorenewable thermoplastic adhesive component, such as an aqueous dispersion of natural rubber latex or polylactic acid.

16. The adhesive according to any one of the preceding claims, characterized in that The molar ratio of SiO2 to Na2O in the water glass is between 4 and 1.5, preferably between 3.8 and 2.0, more preferably between 3.5 and 2.5, even more preferably between 3.5 and 2.

8.

17. The adhesive according to any one of the preceding claims, characterized in that The adhesive contains one or more of a waterproof additive, a catalyst, a dye, a pigment, a flame retardant, a cold adhesion improver, or a foaming agent.

18. The adhesive according to any one of the preceding claims, characterized in that The binder is a liquid and the powder is suspended in the binder.

19. The adhesive according to any one of the preceding claims, characterized in that The particle size distribution of the powder by volume measured by laser diffraction in aqueous dispersion is D 50 The value is less than 200 microns, preferably less than 100 microns, more preferably less than 50 microns, and even more preferably less than 30 microns.

20. The adhesive according to any one of the preceding claims, characterized in that The particle size distribution of the powder by volume measured by laser diffraction in aqueous dispersion is D 90 The value is less than 200 microns, preferably less than 100 microns.

21. A product, wherein the product comprises particles, fibers, layers, bundles or components; wherein the particles, fibers, layers, bundles or components are bound together using a binder according to any one of the preceding claims in a pressing process at elevated temperature, wherein water evaporates from the binder and the binder provides bonding of the particles, fibers, layers, bundles or components; Wherein in the product, the mass ratio of the total amount of particles, fibers, layers, bundles or components to the solid content of the binder is between 99:1 and 92:8, preferably between 98:2 and 95:

5.

22. The product according to claim 21, wherein the mass ratio of the solids of the crosslinking agent in the adhesive to the total amount of particles, fibers, layers, bundles of the product is between 0.5% and 2% by mass, preferably between 0.75% and 1.75% by mass, more preferably between 1% and 1.5% by mass.

23. The product according to any one of the preceding claims 21-22, characterized in that The product is a board, for example a wood fiberboard, such as an MDF board or a HDF board, a particleboard, an OSB (Oriented Strand Board) board or a laminate.

24. The product according to any one of the preceding claims 21-22, characterized in that The product is a molded part, such as a pallet block.

25. The product according to any one of the preceding claims 21 to 24, characterized in that The particles, fibers, layers, bundles or components are wood-based or cellulose-based, such as bamboo, straw, reed, hemp, palm, miscanthus, bagasse, molasses, or agricultural waste streams.

26. A method for preparing a product, wherein the method comprises the following steps - providing a quantity of particles, fibers, layers, bundles or components; - applying a binder according to any one of the preceding claims 1 to 20 to the particles, fibers, layers, bundles or components; - shaping the mixture of the particles, fibers, layers, bundles or components and the binder, for example in the form of a sheet; - curing the binder at elevated temperature and under pressure, wherein water evaporates from the binder, and wherein curing of the binder results in a product in which the particles, fibers, layers, bundles or components are bonded together by the binder.

27. The method according to claim 26, characterized in that The particles, fibers, layers, bundles or components are wood-based or cellulose-based, such as bamboo, straw, reed, hemp, palm, miscanthus, bagasse, molasses, or agricultural waste streams.

28. The method according to any one of the preceding claims 26-27, characterized in that In the product, the mass ratio of the total amount of particles, fibers, layers, bundles or components to the solid content of the binder is between 99:1 and 92:8, preferably between 98:2 and 95:

5.

29. A method according to any one of the preceding claims 26 to 28, characterised in that The product is a board, for example a wood fiber board, such as an MDF board or a HDF board, a particleboard, an OSB (Oriented Strand Board) board or a laminate, or a molded part, such as a pallet board.

Citation Information

Patent Citations

  • Binder composition for chip like and / or fibrous material

    CA2019382A1

  • Method for the production of fire-resistant moulded wood fibre pieces

    US20060163769A1

  • Process for the production of mineral fiber mats

    US4190459A

  • Adhesive for derived wood products

    WO2022049513A1